2005
DOI: 10.1152/ajpendo.00079.2004
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic receptor stimulation attenuates insulin-stimulated glucose uptake in 3T3-L1 adipocytes by inhibiting GLUT4 translocation

Abstract: Activation of the sympathetic nervous system inhibits insulin-stimulated glucose uptake. However, the underlying mechanisms are incompletely understood. Therefore, we studied the effects of catecholamines on insulin-stimulated glucose uptake and insulin-stimulated translocation of GLUT4 to the plasma membrane in 3T3-L1 adipocytes. We found that epinephrine (1 microM) nearly halved insulin-stimulated 2-deoxyglucose uptake. The beta-adrenoceptor antagonist propranolol (0.3 microM) completely antagonized the inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 39 publications
1
32
0
4
Order By: Relevance
“…35) Of the events connecting the administration of CE and the observed phenomena, we are about to verify details of the mechanism related to excitation of the central nervous system and AMPK activity. 36,37) In conclusion, CE had two major functions: i) it up-regulated mitochondrial UCP-1, and ii) enhanced the production and translocation of GLUT4 in the muscle and, at least, the translocation of GLUT4 in adipose tissues. These activities may allow cinnamon to be used in the daily care of diabetes mellitus by its dietary or supplementary use, and in alleviating the long-term complications, including cardiovascular disease, chronic renal failure and retinal damage.…”
Section: Discussionmentioning
confidence: 91%
“…35) Of the events connecting the administration of CE and the observed phenomena, we are about to verify details of the mechanism related to excitation of the central nervous system and AMPK activity. 36,37) In conclusion, CE had two major functions: i) it up-regulated mitochondrial UCP-1, and ii) enhanced the production and translocation of GLUT4 in the muscle and, at least, the translocation of GLUT4 in adipose tissues. These activities may allow cinnamon to be used in the daily care of diabetes mellitus by its dietary or supplementary use, and in alleviating the long-term complications, including cardiovascular disease, chronic renal failure and retinal damage.…”
Section: Discussionmentioning
confidence: 91%
“…Several mechanisms have been proposed by which ␤-adrenergic receptor stimulation may affect insulin-stimulated glucose uptake in 3T3-L1 and rat adipocytes (12,(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…6G, right plot). It has been shown that insulin-stimulated glucose uptake in rat and 3T3-L1 adipocytes could be reduced upon treatment with adrenaline, nor-adrenaline, and isoproterenol (33)(34)(35)(36). Some studies report that ␤-adrenergic receptor agonists attenuate insulin-stimulated glucose uptake by decreasing the translocation of GLUT4 in rat and 3T3-L1 adipocytes (31,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased circulating catecholamines contribute to insulin resistance mainly by stimulating lipolysis in adipose tissue, leading to an increase in circulating nonesterified fatty acids (NEFA) (Lafontan and Langin 2009), and by stimulating both gluconeogenesis and glycogenolysis, contributing to increased hepatic glucose production (Exton and Park 1968;Exton et al 1972). This increase in endogenous glucose production associated with decreased skeletal muscle glucose uptake and decreased fatty acid oxidation (Young et al 1985;Acheson et al 2004;Mulder et al 2005) leads to hyperglycemia and tissue triglyceride deposition, major pathophysiological hallmarks of insulin resistance. We have recently shown that chronic caffeine intake prevents the development of insulin resistance and decreases circulating catecholamines in diet-induced insulin-resistant rats (Conde et al 2012).…”
Section: Introductionmentioning
confidence: 99%